PENGEMBANGAN MODUL PEMBELAJARAN MENULIS TEKS EKSPOSISI DENGAN MODEL PROBLEM BASED LEARNING - Hasanah, Zulfa; Asri, Yasnur; Abdurahman, Abdurahman (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ The purpose of this study was to describe the development of learning modules for writing exposition text Problem Based Learning model with a valid, practical, and effective . This type of research was the development of research methods of research and development (R&D). This study uses a model of the development of Four-D (4-D) were simplified into 3-D. The results of the study is the product of the learning modules write exposition text model Problem Based Learning for students of class X. The level of validity of the module is 89.66 % with the category of very valid . Level module practicalities by teachers was 90.44 % categorized as very practical . Level practicalities of modules by students was 91.37% categorized as very practical . Values module effectiveness was 87.92 % with a very good category.Â Kata Kunci: pengembangan, problem based learning, eksposisi